New morphological information on the ptyctodontid fishes (Placodermi, Ptyctodontida) from Western Australia - Trinajstic, Kate; Long, J.; Johanson, Z.; Young, G.; Senden, T. (Taylor & Francis Inc., 2012)
A full description of a complete and articulated, three-dimensionally preserved, placoderm fish, Materpiscis attenboroughi (Ptyctodontida), from the Late Devonian Gogo Formation is presented. The jaw articulation is unique in being preserved in situ, providing new morphological information on the articulation of the quadrate, metapterygoid, and labial skeleton. In addition, separate hyoid and opercular cartilages are identified, thus confirming their presence for the first time within placoderms. Preserved orbital ossifications indicate an anteriomesial orientation of this braincase region. The complete scapulocoracoid provides additional morphological information on the pectoral fin articulation. A new specimen of Austroptyctodus gardineri preserving the anterior portion of the head and jaws allows for revised descriptions of the endocranium and visceral skeleton, including the most complete endocranial ossifications recovered to date. As well, elements of the labial skeleton not known previously in ptyctodonts are preserved. Small amounts of soft tissues are recovered from Materpiscis,and extensive postcranial body muscle from Austroptyctodus. This new material resolves several questions regarding cranial and postcranial morphology of the Ptyctodontida. Moreover, similarities in placoderm and chondrichthyan pelvic fins and reproductive structures (claspers) suggest early parallel expression of HoxD and sonic hedgehog genes (shh), potentially representing the first evidence for expression of these genes in placoderms.